the Factors associated with migraine among medical students at the University of Parakou (Benin) - Gounongbe ACF,; Mikponhoué RCN,; Adoukonou T,; Mama Cissé I,; Hinson AV,; Djidonou A, (IJRDO-Journal of Applied Science, 2019)
Introduction: The prevalence of migraine in the student population is high with a significant impact on performance. The purpose of this study was to determine the factors associated with migraine among medical students at the University of Parakou. Method: This is a descriptive, cross-sectional analytical study that involved medical students enrolled in the 2013-2014 academic year. The latter were subjected to a questionnaire describing the characteristics of migraine complemented by an evaluation scale. The data was analyzed by EPI Info software version 3.5.3. The Chi 2 test allowed comparisons with a significance level of 5%. Results: A total of 209 students including 132 (63.2%) males were included. Students aged 20 to 25 accounted for 56.9% of the population. The prevalence of migraine was 13.4% (95% CI [9.1 - 18.8]). It was significantly higher among those under 18 years of age (p = 0.049), girls (p = 0.009), students living with family, guardianship or co-location (p = 0.002); during the first two years of study and at the end of the cycle (p = 0.04).Conclusion: The prevalence of migraine in the student population is high and multifactorial etiologies; prevention measures to prevent school failure.